Efektivitas Kinerja Manajemen Sumber Daya Manusia Perguruan Islam Cerdas MurniTembung Deli Serdang - Fajrina Ulfa; Nurmadiah Nurmadiah; Emilda Sulasmi (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2023)
The objectives of this research are: (1) knowing the planning and procurement of human resources at the Yayasan Adlin Murni, Perguruan Islam Cerdas Murni, (2) knowing the development of human resources at the Yayasan Adlin Murni, Perguruan Islam Cerdas Murni, (3) Knowing how to maintain human resources at the Yayasan Adlin Murni, Perguruan Islam Cerdas Murni. The research design used in this study is qualitative with the type of case study research. The stages of research are the pre-research stage, the research stage, the data analysis stage, and the data reporting stage. The research subject in this study is the Adlin Murni Foundation, Pure Intelligent Islamic College and the object of research is teachers and employees who are in the Yayasan Adlin Murni, Perguruan Islam Cerdas Murni Training In human resource planning, recruitment is carried out internally and externally. The internal recruitment system is carried out through interviews, quranic reading tests and microteaching. Human resource development is carried out by directing teachers and employees to attend training, but the foundation is still constrained in carrying out training independently. For the maintenance of human resources, it is carried out by providing compensation in the form of incentives and rewards. The conclusion of this research is: (1) human resource planning is carried out with an internal and external recruitment system,(2) human resource development at the Yayasan Adlin Murni, Perguruan Islam Cerdas Murni is carried out by participating in various trainings, (3) maintenance of human resources at the Yayasan Adlin Murni, Perguruan Islam Cerdas Murni is carried out by providing compensation in the form of incentives and rewards.